snRNA-seq reveals subcutaneous white adipose tissue remodeling upon return to thermoneutrality after cold stimulation - Yusha Yang; Yusha Yang; Guanyu Zhang; Ting Yi; Ting Yi; Shuran Yang; Shuran Yang; Shuai Wu; Yongqiang Zhang; Li Zhang; Xi Li; Xiuxuan Wu; et al. (Frontiers in Cell and Developmental Biology)
IntroductionCold stimulation induces browning of subcutaneous white adipose tissue (sWAT), making it a prime target for treating obesity and metabolic disorders. However, this remodeling is reversible: upon return to thermoneutrality (rewarming), sWAT whitens and loses its enhanced metabolic functions. Given the limited understanding of the microscopic dynamic changes and underlying mechanisms during this process, we established a temporally dynamic mouse model spanning the entire period from cold stimulation to the return to thermoneutrality, with inguinal sWAT (iWAT) selected as the study subject.MethodsBased on preliminary data demonstrating stabilization in iWAT histology, expression levels of key thermogenic proteins, and the bulk transcriptome, we selected the two-week time point after the return to thermoneutrality for detailed analysis. Subsequently, we employed single-nucleus RNA sequencing (snRNA-seq) to comprehensively characterize iWAT cellular dynamics during cold stimulation and the subsequent two-week period after the return to thermoneutrality.ResultsOur findings revealed that while iWAT phenotypically reverts to a white state after 2 weeks of rewarming, as evidenced by structural, functional, and bulk transcriptomic characteristics, significant cold-induced molecular and cellular signatures persist. Specifically, we observed altered differentiation trajectories in both adipose stem and progenitor cells (ASPCs) and adipocytes, suggesting dedifferentiation and reprogramming tendencies. Furthermore, the ANGPTL signaling pathway, activated in thermogenic adipocyte subpopulation A3 during cold stimulation, remained active and influenced cell-cell communication even after the loss of thermogenic capacity.Discussionhese findings provide novel insights into elucidating the complex cellular and molecular mechanisms underlying the temperature-dependent plasticity of iWAT, and suggest that the ANGPTL signaling pathway may play a potential role in maintaining the white phenotype of iWAT after withdrawal from cold stimulation.